What are investors afraid of? Finding the big bad wolf - Barbara Alemanni; Pierpaolo Uberti (International Journal of Financial Studies, 2019)
The aim of financial institutions and regulators is to find an effective way to measure the risk profile of different segments of investors. Both economists and psychologists developed several methodologies to elicit and assess individual risk attitude, but these are not perfect and show several drawbacks when used in practice. Thanks to a unique database of around 15,000 investors, this paper combines survey-based evidence with revealed preferences based upon observed asset allocation. This paper confirms some results known in the literature like the gender and age differences in risk-taking. Moreover, the behavioral clustering approach used for the analysis is useful in an inferential framework. The segments built starting from the questionnaire permit to 'forecast' the individual risk attitude that is described by the individual choices in terms of asset allocation. Loss aversion per se is a relevant variable in explaining financial risk-taking.
Keywords: D14; D18; G11; G41; 330; risk profile; behavioral finance; loss aversion; investors’ clustering; investors’ protection